The Use of Mixed Populations of Saccharomyces cerevisiae and S. kudriavzevii to Reduce Ethanol Content in Wine: Limited Aeration, Inoculum Proportions, and Sequential Inoculation - Alonso-del-Real, Javier; Contreras-Ruiz, Alba; Castiglioni, Gabriel L.; Barrio, Eladio; Querol, Amparo (Frontiers in Microbiology, 2017)
Saccharomyces cerevisiae is the most widespread microorganism responsible for wine alcoholic fermentation. Nevertheless, the wine industry is currently facing new challenges, some of them associate with climate change, which have a negative effect on ethanol content and wine quality. Numerous and varied strategies have been carried out to overcome these concerns. From a biotechnological point of view, the use of alternative non-Saccharomyces yeasts, yielding lower ethanol concentrations and sometimes giving rise to new and interesting aroma, is one of the trendiest approaches. However, S. cerevisiae usually outcompetes other Saccharomyces species due to its better adaptation to the fermentative environment. For this reason, we studied for the first time the use of a S. kudriavzevii strain, CR85, for co-inoculations at increasing proportions and sequential inoculations, as well as the effect of aeration, to improve its fermentation performance in order to obtain wines with an ethanol yield reduction. An enhanced competitive performance of S. kudriavzevii CR85 was observed when it represented 90% of the cells present in the inoculum. Furthermore, airflow supply of 20 VVH to the fermentation synergistically improved CR85 endurance and, interestingly, a significant ethanol concentration reduction was achieved.